Pengaruh Paparan Berita Kriminal terhadap Tingkat Ketakutan terhadap Kejahatan pada Masyarakat di Provinsi Sulawesi Selatan - Anggreni Thamrin, Dian; Ramli, Abu Rizal Fatwa; Fathurahman, Fikry (Jurnal Litigasi Amsir, 2025)
This study aims to examine the influence of exposure to crime news on the level of fear of crime among the public in South Sulawesi Province. The background of this research is driven by the increasing intensity of crime reporting across various mass media platforms, particularly social media and online news portals, which have the potential to affect public perceptions and psychological conditions related to community safety. The study employed a quantitative method using a survey approach involving 115 respondents from various districts and cities in South Sulawesi. Data analysis techniques included descriptive statistics, Pearson correlation, and simple linear regression tests. The results reveal a significant positive relationship between the habit of consuming crime news and the level of fear or anxiety about crime (r = 0.590; p < 0.01). Regression analysis shows that the variable of crime news exposure has a significant effect on fear levels (β = 0.639; p = 0.000), with a contribution of 34.8%. These findings indicate that the more frequently individuals are exposed to crime related news, the higher their perceived fear of crime. This research provides important implications for public information management and media literacy, encouraging individuals to be more critical in receiving and interpreting crime news.